Design of Paper Foil and Laminating Machine as Lining Material for Paper Bags - Wahyudi, Pongky Lubas; Cahyo, Yusuf Eko Nur; Budiyanto, Risandie Octafian; Wulandari, Anita (Universitas Muhammadiyah Yogyakarta, 2025)
In order to enhance the contribution of MSMEs as a key driver of Indonesia’s economic growth, the development of small- to medium-scale production machines is essential. This is particularly important as MSMEs face increasing competition and more complex customer demands. This study aims to design and develop a simple production machine using CAD software and Autodesk Inventor to improve productivity and quality in the paper bag manufacturing process. Currently, production is carried out manually, resulting in limited capacity and product quality. The machine being designed serves to perform the paper gluing and rolling processes with foil lamination. The design integrates the gluing and rolling mechanisms into a single unit equipped with an automatic rotating system. This setup significantly reduces production time, thereby increasing both capacity and quality compared to the manual process. Simulation analysis of force, stress, and safety factor was carried out assuming the frame receives a load of 120 N, based on conditions close to reality. The results show a maximum Von Mises stress of 97.91 MPa and a minimum of 0 MPa. The maximum displacement is 0.5844 mm, and the minimum is 0 mm. The safety factor at the top frame section is 2.55 ul. Meanwhile, for testing under a 12 kg load, the results show a maximum Von Mises stress of 108.8 MPa, a displacement of 0.6488 mm, and a safety factor of 2.3 ul.